The Role of Law in Addressing Environmental Crimes Caused by Companies - Murtono Murtono; Mohamad Tohari; Wieke Dewi Suryandari (CV. Green Publisher Indonesia, 2026)
Environmental crimes committed by corporations have become a global issue requiring serious attention within the legal system. Irresponsible exploitation of natural resources, environmental pollution, and ecosystem destruction are the primary forms of environmental crimes frequently perpetrated by corporations. These crimes not only threaten environmental sustainability but also cause significant economic and public health harm to society. The role of law is therefore crucial in preventing and addressing environmental crimes committed by corporations. This study aims to analyze how law functions in preventing and addressing corporate environmental crimes through administrative, civil, and criminal legal instruments. A normative juridical research method is employed with a regulatory approach supported by relevant legal theories. The data consist of primary legal materials, including applicable laws and regulations, as well as secondary legal materials comprising scholarly literature, legal journals, and other legal documents. This study examines various legal instruments that have been implemented to control corporate environmental crimes, including licensing regulations, administrative sanctions, civil lawsuits, and criminal penalties for companies and their directors. Furthermore, this research addresses challenges in environmental law enforcement, such as weak oversight, political and economic interests, and a lack of inter-agency coordination. A deeper understanding of the role of law in this area is expected to contribute to the strengthening of environmental regulations to ensure corporate compliance with sustainable environmental standards.